The Effect of Game Style Using Training Mask on Some Functional Indicators and Performance Endurance In Advance 3 × 3 basketball players - Safaa, Haneen; Rrfat, Luay Sami (Journal of Physical Education, 2019)
The research aim at developing some functional variables like pulse during rest and effort, and performance endurance in advance female 3×3 basketball players as well as designing a test for measuring performance endurance. The researchers used the experimental method on (3) female basketball players. The exercises were applied using game method with training mask in (29) training session for (10) weeks with (3) training sessions per week. The results showed that game style using training mask developed physical abilities in general and performance endurance in particular. In addition to that, game style using training mask did not develop lactic acid concentration during rest.